Medical Certification of Cause of Death (MCCD) with special reference to deaths due to Coronavirus Disease 2019 (COVID–19) - Wankhade, Toshal; Shrigiriwar, Manish; Ramchandra Sane , Mandar (Journal of Indian Academy of Forensic Medicine, 2021)
In communicable diseases pandemic, death certificates are vital for public health surveillance and deaths. A uniform protocol is expected for the same as inconsistent death certification protocol may lead to misleading death-related statistics. Deaths due to COVID-19 may occur in varying circumstances and even in patients without prodromal symptoms. Similarly, deaths in suspected COVID-19 patients may be misdiagnosed or certified. An accurate certification of deaths due to COVID–19 infections is vital as it is critical for ongoing public health surveillance and response. Similarly, e-Mortality (e-Mor) software, hosted by The National Centre for Disease Informatics and Research (NCDIR) should be used as it records details of the death of all institution and non-institution based deaths with a guide to prevent errors in the cause of death. The article is intended to guide health professionals on proper cause of-death certification for cases where confirmed or suspected COVID–19 infection resulted in death.